Cosmological Evolution With Negative Energy Densities - Saharian, A. A.; Avagyan, R. M.; Bezerra De Mello, E. R.; Kotanjyan, V. Kh.; Petrosyan, T. A.; Babujyan, H. G. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
For general number of spatial dimensions we investigate the cosmological dynamics driven by a cosmological constant and by a source with barotropic equation of state. It is assumed that for both those sources the energy density can be either positive or negative. Exact solutions of the cosmological equations are provided for flat models. For models with curved space and with zero cosmological constant the general solutions are expressed in terms of the hypergeometric function. The qualitative evolution is described for all values of the equation of state parameter. We specify the values of that parameter and the combinations of the signs for the cosmological constant and matter energy density for which the cosmological dynamics is nonsingular. An example is considered with positive cosmological constant and negative matter energy density induced by the polarization of the hyperbolic vacuum. Для произвольного числа пространственных измерений исследована космологическая динамика, управляемая космологической постоянной и источником с баротропным уравнением состояния. Предполагается, что для обоих источников плотность энергии может быть как положительной, так и отрицательной. Для плоских моделей приведены точные решения космологических уравнений. Для моделей с искривленным пространством и с нулевой космологической постоянной общие решения выражаются через гипергеометрическую функцию. Качественная эволюция описана для всех значений параметра уравнения состояния. Выделены значения этого параметра и комбинации знаков для космологической постоянной и плотности энергии материи, для которых космологическая динамика несингулярна. Рассмотрен пример с положительной космологической постоянной и отрицательной плотностью энергии вещества, индуцированной поляризацией гиперболического вакуума.
Keywords: Astrophysics